Physical characterization of Bacteroides fragilis R plasmid pBF4. - Welch, R A (1981)
Bacteroides fragilis V479-1 has previously been shown to harbor a self-transmissible 27 X 10(6)-dalton plasmid (pBF4) which confers lincosamide-macrolide resistance. The present study has focused on the physical properties of pBF4. The plasmid was found to be present in 1 to 2 copies per chromosomal equivalent. pBF4 was genetically stable, although spontaneously occurring plasmidless segregants could be detected at low frequency (approximately 1%). This frequency was unaffected by growth of cells in ethidium bromide. About one-third of all spontaneously occurring macrolide-lincosamide-sensitive clones of strain V479-1 were found to contain pBF4 molecules that carried deletions. Ten independently obtained deletion derivatives of pBF4 from lincosamide-macrolide-sensitive strains were compared with the parental pBF4 by restriction endonuclease cleavage analysis. A restriction site map of pBF4 was constructed, and the location of the deletions was approximated. Self-annealed pBF4 molecules, examined by electron microscopy, revealed the presence of two pairs of inverted repeat (IR) sequences on the plasmid. IR-1 was about 400 base pairs in length, and its two component members were separated by an intervening sequence of about 15 kilobases. IR-2 was about 75 base pairs in length, and its component members were separated by 4.2 kilobases. Each of the deletions of pBF4 studied had a terminus at or near the same IR-2 sequence.